Fluoridated orthodontic adhesives: Implications of release and recharge and their impact on shear bond strength in demineralized tooth surfaces - Mohammed Sabah Yaseen; Neam F Agha; Raya Jasim (Tabriz University of Medical Sciences, 2023)
Background. This study measured fluoride release from a light-cured orthodontic adhesive resin (Vega type) at three time intervals (one day, one week, and one month), investigated the rechargeability of the resin, and assessed its impact on shear bond strength in demineralized tooth surfaces. Methods. This study used 30 recently extracted upper premolar teeth to explore the effects of fluoride release over specific time intervals. The teeth underwent demineralization and were categorized into groups based on time intervals: one day, one week, and one month. Subgroups within each interval underwent fluoride recharging through fluoride varnish application. Fluoride release and shear bond strength were assessed after etching with phosphoric acid gel, applying the orthodontic adhesive, and curing. The samples were stored in deionized water. Fluoride quantification used a selective electrode, while shear bond strength assessment employed a universal testing machine. Finally, statistical analysis of the data was performed using SPSS 22. Results. The study found that after one month, the adhesive had the highest fluoride release and shear bond strength mean values. There were significant differences in fluoride release and shear bond strength between the various groups studied. Conclusion. The application of fluoride varnish around the orthodontic bracket resulted in a positive effect on the shear bond strength of the bracket.